1996
DOI: 10.1677/joe.0.1510259
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hormone and metabolic responses in simulated shift work

Abstract: This study was designed to investigate postprandial responses to a mixed meal in simulated shift work conditions. Nine normal healthy subjects (six males and three females) were studied on two occasions at the same clock time (1330 h) after consuming test meals, first in their normal environment and secondly after a 9 h phase advance (body clock time 2230 h). Plasma glucose, insulin, glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-1 (GLP-1), triacylglycerol (TAG) and non-esterified fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
3
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 13 publications
9
105
3
3
Order By: Relevance
“…The present study showed that the adverse effects of circadian misalignment during a forced desynchrony protocol are also observed in conditions more similar to those experienced by real-life shift workers, and are sustained over a number of days of repeated exposure. Our data are also consistent with the general notion that various forms of circadian disruption (e.g., SCN lesions, clock gene mutations, continuous light exposure, and simulated shift work) can impair glucose metabolism (19,20,26,28,29).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study showed that the adverse effects of circadian misalignment during a forced desynchrony protocol are also observed in conditions more similar to those experienced by real-life shift workers, and are sustained over a number of days of repeated exposure. Our data are also consistent with the general notion that various forms of circadian disruption (e.g., SCN lesions, clock gene mutations, continuous light exposure, and simulated shift work) can impair glucose metabolism (19,20,26,28,29).…”
Section: Discussionsupporting
confidence: 90%
“…An endogenous circadian rhythm in circulating glucose and insulin levels has been detected in humans by using intensive protocols performed under constant conditions ("constant routine" protocols) or when the behavioral cycle influences are accounted for by evenly distributing them across the entire circadian cycle ("forced desynchrony" protocols) (4,(10)(11)(12)14). In addition, circadian misalignment-as occurs in shift workers-also leads to impaired glucose metabolism in rodents and humans (10,(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Significancementioning
confidence: 99%
“…Others have examined the effect of simulated night shift work on postprandial glucose and insulin with varied results (18,19). Interpretation of these studies is complicated due to differences in premeal conditions between the night and day shifts (e.g., duration of wakefulness before test meals), such that the effects of circadian misalignment alone could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chronic exposure to shift work increases risk of metabolic syndrome (87) , as well as CHD, stroke and stroke-related mortality, and type 2 diabetes (88)(89)(90)(91) . Laboratory studies in human subjects have shown that consumption of meals during the biological night results in increased postprandial glucose, insulin and TAG relative to daytime meals (92)(93)(94) . Additionally, rotating shiftwork is associated with higher fasting TAG and free fatty acids, and lower HDLcholesterol (95,96) .…”
Section: Circadian Misalignment and Metabolic Dysfunctionmentioning
confidence: 99%